Blau Syndrome and Early-Onset Sarcoidosis: A Six Case Series and Review of the Literature - Ayşenur PAÇ KISAARSLAN; Betül SÖZERİ and Nihal ŞAHİN and Sümeyra ÖZDEMİR ÇİÇEK and; yde GÜNDÜZ and; n DEMİRKAYA and Afig BERDELİ and Serdal SADET ÖZCAN and Hakan PORAZOĞLU and Ruhan DÜŞÜNSEL (Archives of Rheumatology, 2020)
Objectives: This study aims to discuss the clinical, laboratory and genetic findings, and treatment options for six patients who were diagnosed with Blau syndrome (BS)/early-onset sarcoidosis (EOS). Patients and methods: The study included four patients (2 males,2 females; mean age 7 years; range 4 to 10 years) with EOS and two siblings (1 male, 1 female; mean age 10 years; range, 9 to 11 years) with BS. Age, age of initial symptoms, age of diagnosis; articular involvement, presence of uveitis, dermatitis, or fever, other organ involvement, laboratory findings, results of metabolic tests for mucopolysaccharidosis and mucolipidosis, results of genetic, pathologic, and immunologic tests, radiologic findings to evaluate skeletal dysplasia, and treatment options were collected. Results: The median age at diagnosis of all patients was 6 years (range, 1 to 10 years). Five patients had camptodactyly and bilateral boggy synovitis in the wrists and ankles, one had granulomatous inflammatory changes in the liver and kidney biopsy, and one had attacks of fever and granulomatous dermatitis. None had uveitis. The detected mutations in nucleotide-binding oligomerization domain containing 2 (NOD2) were P268S (rs2066842), M513T (rs104895473), R702W (rs2066844), V955I (rs5743291), H343Y (rs199858111), and M491L (16:50745293). The treatments of patients included corticosteroids, non-steroid anti-inflammatory drugs, methotrexate, infliximab, adalimumab, anakinra, and canacinumab. Conclusion: Camptodactyly and boggy synovitis are important signs of BS/EOS. Methotrexate and tumor necrosis factor blockers are more effective in patients with predominantly articular symptoms. In patients 5 and 6 and their mother, we determined a novel M491L mutation in the NOD2 gene. Currently, this work is in progress towards identifying the pathogenesis and treatment options for this disease.